FAKTOR PENENTU DALAM MENDORONG NIAT MEMBELI "ODADING MANG OLEH" - Auliawati Nuraieni, Firda; Haryanto, Niko Dwi; Pradesa, Hafid Aditya (Jurnal Ekonomi Manajemen, 2021)
ABSTRACTThe purpose of this study was to examine the important determinants of the intention to buy the product "Odading Mang Oleh" (a food product in Bandung that was viral on social media) in terms of E-Word of Mouth (E-WOM), brand credibility, and brand image. This study uses quantitative methods, using 112 respondents who perceive each research instrument that is distributed online. The research findings reveal that E-WOM does not have a significant effect on the intention to buy "Odading Mang Oleh", while credibility and brand image have an important impact on the intention to buy the product. The conclusions may not be generalizable because not all areas were represented in this study. In future studies, a larger and more inclusive sample would help to overcome this limitation. This study provides practical information about the exploration of important determinants of product purchasing decisions in terms of e-word of mouth, brand credibility, and the brand image of a product that was viral.